Analisis Kesulitan Belajar Siswa Kelas V pada Materi Bangun Ruang Kerucut dan Prisma SDN Batujaya Kecamatan Batu Ceper - Ramdhan, Savina Nurrahmadanti; Unaenah, Een; Oktavia, Dela; Luftiyah, Vivi (MASALIQ, 2022)
The purpose of this study is to describe: 1) Difficulty learning mathematics in class V even semester at SDN Batujaya, Batu Ceper District, 2) Factors causing difficulty in learning mathematics in class V SDN Batujaya, Batu Ceper District. This research method uses a qualitative description where the instruments used are interviews, observation sheets, learning outcomes tests and documentation. The sample of this study were 25 fifth grade students at SDN Batujaya, Batu Ceper sub-district with 12 male students and 13 female students. Data were analyzed by data reduction steps, data presentation, and drawing conclusions. The results showed that from 25 students there were 5 people who did not complete learning mathematics to achieve KKM. The difficulties encountered were: (a) Difficulty in memorizing multiplication (b) Difficulty in determining the formula that should be used to solve the problem (c) Difficulty in calculating using multiplication. The causes of learning difficulties in mathematics are students who do not understand mathematics, especially conical shapes and prism, students do not pay attention to the teacher's explanation when learning activities take place in front of the class, students do not practice math problems.